Development of visual surveillance standardization - Yuan ZHANG; Ning CAO; Doudou HU (Dianxin kexue)
The standardization of visual surveillance in major standard organizations both domestic and international was focused on,and the progress of the visual surveillance standards in ITU-T,ONVIF,IEC,ISO,PSIA,HDcctv,IEEE,3GPP,ETSI,TC100,CCSA,AVS and National Information Technical Standardization Committee was introduced.The latest development in standardization area such as visual surveillance systems,architecture,terminals,codecs,intelligent applications,big data applications,cloud storage,cloud computing,edge storage and edge computing were introduced.On this basis,the future research areas of product development and standardization of visual surveillance were discussed.The visual surveillance standardization roadmap was laid out,and the future visual surveillance standardization and research fields were proposed.